Strategi Pemenuhan Kebutuhan Ekonomi Janda Di Desa Pa’bumbungang - Mrs. Hariani; Dimas Ario Sumilih; Mubarak Dahlan (Rayhan Intermedia, 2022)
This study aims to determine the views of widows in Pa'bumbungan village about living and meeting their needs, the strategy of widows to divide their time between working to meet economic needs and educating their children, the views of the surrounding community about widows and their work. In this study, qualitative data were analyzed and descriptively used. Data collection techniques used observation, interviews, and documentation methods involving 8 (eight) individuals, namely 5 (five) widows and 3 (three) local people. The theory used is Structural Functionalism. The results showed that the widow's view of life based on Kluckhohn's opinion there are five main problems in human life or in the context of the widow itself including: (a) the nature of the widow's life, (b) the nature of the widow's work, (c) the nature of the widow's position in the living room. and time, (d) the nature of the widow's relationship with the natural surroundings, (e) the nature of the widow's relationship with each other. Fulfilling the economic needs of widows in Pa'bumbungan village by working. The work they do is cultivating private gardens, being harvest workers, opening a shop and selling clothes.